The Fatimid Empire - Brett, Michael 1934- (The Edinburgh history of the Islamic empires, 2017)
The Fatimid empire in North Africa, Egypt and Syria was at the centre of the political and religious history of the Islamic world in the Middle Ages, from the breakdown of the 'Abbasid empire in the tenth century, to the invasions of the Seljuqs in the eleventh and the Crusaders in the twelfth, leading up to its extinction by Saladin. As Imam and Caliph, the Fatimid sovereign claimed to inherit the religious and political authority of the Prophet, a claim which inspired the conquest of North Africa and Egypt and a following of believers as far away as India. The reaction this provoked was crucial to the political and religious evolution of mediaeval Islam. This book combines the separate histories of Isma'ilism, North Africa and Egypt with that of the dynasty into a coherent account. It then relates this account to the wider history of Islam to provide a narrative that establishes the historical significance of the empire.